Copper/zinc superoxide dismutase-like immunoreactivity in the metamorphosing brain of the sphinx moth Manduca sexta. - Schachtner, J; Huetteroth, W; Nighorn, A; Honegger, H (2004)
Cu/Zn superoxide dismutase (SOD) is part of the defense mechanism that protects cells from being damaged by reactive oxygen species. During metamorphosis of the nervous system, neurons undergo various fates, which are all coupled to high metabolic activities, such as proliferation, differentiation, pathfinding, and synaptogenesis. We describe the pattern of SOD immunoreactivity of identified neurons and neuron groups in the brain of Manduca sexta from the late larva through metamorphosis into adult. We focused on neurons of the developing antennal lobes, the optic lobes, and the central brain. Our results indicate the transient expression of SOD during phases in which the neurons develop their final adult identities. Our data also suggest that the SOD immunoreactivity may be used as an indicator for the period in which developing neurons form their synapses. We also observed SOD immunoreactivity within nitric oxide-sensitive cells as characterized by immunolabeling against 3'5'-cyclic guanosine monophosphate and soluble guanylyl cyclase, a novel finding in insects.